2016
DOI: 10.1007/s00268-016-3775-8
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective One‐Year Estimation of the Volume and Nature of Surgical and Anaesthetic Services Delivered to the Populations of the Fako Division of the South‐West Region of Cameroon: An Urgent Call for Action

Abstract: The volume of surgery delivered in the Fako is far below the minimum rates required to meet up with the most basic requirements of the populations. It is likely that most of these surgical needs are left unattended. A community-based assessment of unmet surgical needs is necessary to accurately estimate the magnitude of the problem and guide surgical capacity improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…This further explains the high mortality noted in the series and related studies in Africa. The high mortality associated to our series and related studies in Ethiopia [ 7 ] and Tanzania [ 10 ] can further be explained by global shortage of surgical and anaesthetics services in these regions [ 20 , 21 ]. The number of cases of IHPS that remain undiagnosed in the community may be higher than expected as most of these later die of severe dehydration and sepsis.…”
Section: Main Textmentioning
confidence: 86%
“…This further explains the high mortality noted in the series and related studies in Africa. The high mortality associated to our series and related studies in Ethiopia [ 7 ] and Tanzania [ 10 ] can further be explained by global shortage of surgical and anaesthetics services in these regions [ 20 , 21 ]. The number of cases of IHPS that remain undiagnosed in the community may be higher than expected as most of these later die of severe dehydration and sepsis.…”
Section: Main Textmentioning
confidence: 86%
“…This is probably related to the presence of an orthopaedic surgeon in most teaching hospitals. The low exposure to hernia repair and appendectomy is probably explained by the overall low rates of performance of these procedures in low‐income countries as compared to high‐income countries [2, 2628] and is probably explained by the overall poor level of provision of surgical services [4]. Comparable rates of exposures have been reported previously for these two procedures of critical importance [25].…”
Section: Discussionmentioning
confidence: 99%
“…The need to increase the number of surgical interventions carried out in Africa (and the world at large) [3, 4, 12, 13] and many countries is well established, and many countries fail to meet the basic surgical needs of their populations due to low surgical workforce [1, 6, 14, 15]. Thus, general practitioners and other non‐specialist staff need to perform a range of surgical procedures in order to help meet the surgical needs of the population of less developed [8, 9, 16] and even developed societies [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean national surgical specialist workforce density is about 1.15 per 100,000 population, significantly below the LCOGS target of at least 20 surgical specialists per 100,000 population [ 7 ]. Although national-level data is not available, a recent study found that 2,460 surgical procedures per 100,000 population are conducted by a handful of specialist surgeons in the Fako Division (South West, Cameroon) [ 8 , 9 ]. Furthermore, people in Cameroon with SOTA-related pathologies face significant financial hardship as a result of seeking SOTA care.…”
Section: Introductionmentioning
confidence: 99%